Struktur Tritangtu pada Siger Aksesoris Pengantin Sunda Priangan - Fadly Fathul Ulum; Endang Caturwati; Heri Herdini (Pascasarjana ISBI Bandung, 2022)
The bride is a symbol of changes in the cycle of human life which is interpreted sacredly. One of the symbols of its sacredness is the use of siger as one of the accessories for Sundanese wedding costume. This paper aims to identify the concept of Sundanese Tritangtu philosophy in Siger Sunda Priangan accessories which cover Sumedang, Sukapura, and Galuh regions. The analysis applies Levi-Strauss structuralism theory, through the stages of elements, binary opposition, transformation and paradigmatic. The three models of Siger Sunda Priangan style, Sumedang style, Sukapura style, and Galuh style were used as the objects of study. The fndings show the same physical structure forms a similar patern, so that the basic structure of Siger crown forms a triple patern in the philosophy of Sundanese people. The same structure of the three Siger forms shows the concepts of surface structure and deep structure in the way of thinking of the Sundanese people. In this context, it means that the form of Siger and the use of Siger in Sundanese brides have standard rules, because they have a sacred meaning.Keywords: Siger Sunda, Tritangtu, Sundanese Bride, Siger ABSTRAKPengantin sebagai simbol perubahan siklus kehidupan manusia yang dimaknai secara sakral. Salah satu simbol kesakralannya berada pada penggunaan siger sebagai salah satu aksesoris kostum pengantin sunda. Tulisan ini bertujuan mengidentifikasi konsep Silih Asah, Silih Asih dan Silih Asuh sebagai komponen dari filsafat Sunda Tritangtu pada aksesoris Siger Sunda Priangan yang meliputi wilayah Sumedang, Sukapura, dan Galuh. Analisis menggunakan teori strukturalisme Levi-Strauss, melalui tahapan elemen-elemen, oposisi binner, transformasi dan paradigmatik. Tiga model Siger Sunda Priangan gaya Sumedang, gaya Sukapura, dan gaya Galuh yang dijadikan objek kajian ditemukan struktur fisik yang sama berbentuk segitiga, sehingga struktur dasar mahkota Siger membentuk pola tiga. Struktur yang sama dari ketiga ragam bentuk siger tersebut menunjukkan konsep surface struktur dan deep struktur filsafat Tri Tangtu. Hal ini dimaknai, bahwa bentuk siger dan penggunaan siger pada pengantin sunda memiliki tata aturan yang baku, karena memiliki makna yang sakral.